2013
DOI: 10.1016/j.injury.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Blunt traumatic aortic injuries of the ascending aorta and aortic arch: A clinical multicentre study

Abstract: Traumatic aortic injuries of the ascending aorta/arch should be considered in any major thoracic trauma patient presenting cardiac tamponade, aortic valve regurgitation and/or myocardial contusion. These aortic injuries are also associated with a high incidence of neurological injuries, which can be just as lethal as the aortic injury, so treatment priorities should be modulated on an individual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…Spinal injuries were reported in 23% of patients . Paraplegia was not described upon admission and after surgery in any of these cases except ours.…”
Section: Literature Reviewmentioning
confidence: 55%
See 1 more Smart Citation
“…Spinal injuries were reported in 23% of patients . Paraplegia was not described upon admission and after surgery in any of these cases except ours.…”
Section: Literature Reviewmentioning
confidence: 55%
“…We reviewed cases of ascending aortic injury from 1998 to present using PubMed with the search terms “traumatic ascending aortic injury.” We found 43 cases (including our present patient presentation) in the literature and details are summarized in Table and Table . There were five cohort observations which included 24 cases (Table ) and 19 case reports (Table ) . The patients demographics were available in a total of 19 cases, which consisted of the majority of male patients with mean age of 45.4 years old (Table ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…73 Many of these patients die immediately, but some present with an acute paraplegia. 73 Many of these patients die immediately, but some present with an acute paraplegia.…”
Section: Traumatic Aortic Injurymentioning
confidence: 99%
“…In addition, other coexistent injuries such as fractured ribs and pulmonary contusion with the same chief complaints may mask the manifestations of cardiac injury. Mosquera et al [7] reported that significant aortic regurgitation (AR) developed in 12% of patients with injuries at the ascending aorta as a consequence of the thoracic trauma. Proposed mechanisms that contribute to BAI include shearing forces, rapid deceleration, hydrostatic forces, and osseous pinch [8].…”
mentioning
confidence: 99%